The effect of cryopreservation on the survivability, viability and motility of Merino (Ovis aries) and African buffalo (Syncerus caffer) spermatozoa - Lambrechts, Helet (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1996.